2006
DOI: 10.1002/jor.20182
|View full text |Cite
|
Sign up to set email alerts
|

Global gene profiling reveals a downregulation of BMP gene expression in experimental atrophic nonunions compared to standard healing fractures

Abstract: Nonunion is a challenging problem that may occur following certain bone fractures. However, there has been little investigation of the molecular basis of nonunions. Bone morphogenetic proteins (BMPs) play a significant role in osteogenesis. However, little is known about the expression patterns of BMPs in abnormal bone healing that results in nonunion formation. These facts prompted us to investigate and compare the gene expression patterns of BMPs and their antagonists in standard healing fractures and nonuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 27 publications
4
79
3
3
Order By: Relevance
“…Dentonin, which is the same as AC-100, promotes dental pulp stem cell proliferation in response to the dentin repair response (34,35). Furthermore, Bmp-2, Dlx5, and Mepe expressions are increased during healing of a bone fracture (36). Our data suggest that BMP-2-induced Mepe and Phex expression are much higher in the early differentiation stage than in the late differentiation stage (Fig.…”
Section: Mepe Expression Is Strongly Stimulated By Bmp-2 Treatment Anmentioning
confidence: 58%
“…Dentonin, which is the same as AC-100, promotes dental pulp stem cell proliferation in response to the dentin repair response (34,35). Furthermore, Bmp-2, Dlx5, and Mepe expressions are increased during healing of a bone fracture (36). Our data suggest that BMP-2-induced Mepe and Phex expression are much higher in the early differentiation stage than in the late differentiation stage (Fig.…”
Section: Mepe Expression Is Strongly Stimulated By Bmp-2 Treatment Anmentioning
confidence: 58%
“…b-Actin was used as an internal control. Relative mRNA expression levels were calculated as described by Niikura et al 18 PCR primers were as follows:…”
Section: Microarray Analysismentioning
confidence: 99%
“…1 By microarray technology the gene expression profiles of BMPs and their antagonists were investigated in standard healing fractures and atrophic nonunions produced by periosteal cauterization at the fracture site. 2 It was shown that the expression of several BMPs and their antagonists was significantly lower in nonunions compared to standard healing fractures. 2 Angiogenesis, the formation of new blood vessels from pre-existing ones, is promoted after fracture to maintain oxygen homeostasis, deliver nutrients, remove waste products, and provide cells and biological mediators.…”
mentioning
confidence: 99%
“…2 It was shown that the expression of several BMPs and their antagonists was significantly lower in nonunions compared to standard healing fractures. 2 Angiogenesis, the formation of new blood vessels from pre-existing ones, is promoted after fracture to maintain oxygen homeostasis, deliver nutrients, remove waste products, and provide cells and biological mediators. Furthermore, angiogenesis plays a pivotal role during intramembranous bone formation and endochondral ossification.…”
mentioning
confidence: 99%